The Influence of Pressure on Local Heat Transfer Rate under the Vapor Bubbles during Pool Boiling - Vladimir Serdyukov; Ivan Malakhov; Anton Surtaev (Energies, 2023)
This paper presents the results of an experimental study on the evolution of a nonstationary temperature field during ethanol pool boiling in a pressure range of 12–101.2 kPa. Experimental data were obtained using infrared thermography with high temporal and spatial resolutions, which made it possible to reconstruct the distribution of the heat flux density and to study the influence of pressure reduction on the local heat transfer rate in the vicinity of the triple contact line under vapor bubbles for the first time. It is shown that, for all studied pressures, a significant heat flux density is removed from the heating surface due to microlayer evaporation, which exceeds the input heat power by a factor of 3.3–27.7, depending on the pressure. Meanwhile, the heat transfer rate in the area of the microlayer evaporation significantly decreases with the pressure reduction. In particular, the local heat flux density averaged over the microlayer area decreases by four times as the pressure decreases from 101.3 kPa to 12 kPa. Estimates of the microlayer profile based on the heat conduction equation were made, which showed the significant increase in the microlayer thickness with the pressure reduction.